The Performance of Civil Servant Employees of the Secretariat of the Regional People’s Representative Council of Klaten Regency - Prasetyo, Yokke Irvan Ade; Istiatin, Istiatin; Sudarwati, Sudarwati (Journal of Business Innovation and Research, 2024)
Leadership, motivation, work discipline, and commitment are the four elements that this study seeks to identify as having an effect on the performance of the civil servant (ASN) employees of the Secretariat of the Regional People’s Representative Council (DPRD) of Klaten regency. The research strategy used in this study is quantitative. There are a total of 38 individuals employed by the ASN at the DPRD Secretariat within the Klaten regency. This research used the census method for sampling, with a total of 38 respondents. Gathering information by use of surveys. Statistical analysis makes use of a number of data analysis procedures, including F tests, t tests, determination coefficients, and double linear regression tests. Leadership, motivation, work discipline, and commitment all have a favorable and substantial effect on the DPRD Secretary of Klaten district's performance, according to the study. Staff performance will be at an all-time high since the secretariat of the DPRD district of Klaten is always working to enhance leadership, motivation, work discipline, and commitment.